Oncological and functional outcomes following treatment of T1a glottic squamous cell carcinoma with transoral laser microsurgery - Dennis E. Curry; David Forner; Matthew H. Rigby; Jonathan R. Trites; Martin Corsten; S. Mark Taylor (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Laryngeal cancers of glottic origin comprise a large proportion of head and neck malignancies. Transoral laser microsurgery (TLM) and radiation therapy are mainstays in the treatment of early stage glottic cancer, but debate persists as to which modality is functionally superior. Furthermore, there is a paucity of North American data related to functional and oncological outcomes in T1a glottic cancer. Here, we assessed oncological and functional outcomes of T1a glottic squamous cell carcinoma (SCC) with TLM to supplement evidence from jurisdictions outside North America. Methods This study is a retrospective cohort study performed from a prospectively collected tertiary center institutional TLM database. Patients who were diagnosed with T1a glottic SCC and underwent TLM as their primary treatment were included. Functional outcomes were analyzed using the Voice Handicap Index-10 (VHI-10) questionnaire. Ultimate control with TLM only was considered to be those patients with locoregional control with repeat TLM procedures, but without addition of other modalities. Student’s t-test was used to test significance and Kaplan–Meier survival analysis was used to assess oncological outcomes. Results 48 patients met study criteria. The mean follow-up time was 74 months. The 5-year locoregional, ultimate control with TLM only and laryngeal preservation rates were 83.2%, 90.4% and 100%, respectively. The overall survival and disease-specific survival were 87.2% and 100%, respectively. VHI-10 scores were available for 13/48 patients and mean scores improved non-significantly from pre-op (mean: 11.23; range: 2 to 30; median: 10) and post op (mean: 7.92; range: 0 to 18; median: 8) scoring (p-value = 0.15). Sub-stratification of voice data revealed a significant improvement between pre and post-operative scores (mean difference − 10.6, 95% CI: − 0.99 to − 20.21, p-value = 0.035) for patients with abnormal pre-operative scores (VHI > 11). Conclusion To our knowledge, the current work represents one of the first North American studies to report both functional and oncologic outcomes for TLM treatment of T1a glottic SCC. The oncologic and functional outcomes presented here add to existing evidence in favor of TLM as a safe and effective primary treatment option for early staged T1a glottic cancer. Graphical abstract